Delivery of a fetus with undiagnosed sacro coccygeal teratoma - Kabadi, Hemalatha Radhakrishna; SR, Chandana Murthy; Shivanna, Mnajunath B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Sacrococcygeal teratoma is the most common tumour of the fetus and neonate with an incidence of 1 in 40000 births. Here we describe the management of an undiagnosed sacrococcygeal teratoma, which is rare in this era.